The Effect Of Disclosure CSR GRI-On Market Reaction In Listed Energy Based Companies In Indonesia - Astrid Maharani; Yusron Rozzaid (Universitas Islam Lamongan, 2022)
This study aims to analyze of the implementation Corporate Social Responsibility (CSR) disclosure on market reaction to energy companies listed on the Indonesia Stock Exchange. The development of previous research, and the effective implementation of the Global Reporting Initiative that uses the 2016 GRI standard which was approved in 2016 by the Global Sustainability Standards Board (GASB) which then effectively applies starting July 1, 2018. The result, GRI standard CSR disclosure has no effect on the market reaction of energy companies listed on the Indonesia Stock Exchange. In the results of this study the possibility of stakeholders other than investors still assume that CSR carried out by the company is oriented to long-term company performance, while the thinking as an investor or potential investor is only about how to optimize short-term company performance.